Parameterisasi Pengontrol Yang Menstabilkan Plant Secara Internal - Kasbawati, Kasbawati (Jurnal Matematika, Statistika dan Komputasi, 2018)
This handing out lifts the problem about parameterization of all controllers that can internally stabilize the given system. Controller parameterization is done as a mean to show that the controller can we shape in so many kinds of parameter. A control problem in this setup is to analyze some specific properties (e.g., stability or performance) of the closed loop system or to design the feedback control K such that the closed loop system is stable in some appropriate sense.